RESPONSIBILITIES OF HEALTH PERSONNEL IN PROVIDING TELEMEDICINE IN MEDICAL PRACTICES IN INDONESIA - Tuti Widyaningrum; Nurul Wahdah N.; Januar Agung Saputera (Faculty of Law, Universitas Pekalongan, 2022)
Legal relationships in telemedicine practice can be differentiated based on timing, the moment when information is transmitted or interactions between individuals involved in telemedicine practice occur . So telemedicine practice can be divided into two types , namely real time ( synchronous telemedicine ) and store-and-forward ( asynchronous telemedicine ). Research Problem Formulation (1) How is the Legal Protection of Patient Personal Data in Health Information Technology Based Health Services? (2) What are the responsibilities of health workers in providing telemedicine in medical practice services in Indonesia? (3) What are the regulations for implementing telemedicine in medical practice services in Indonesia? This type of research is normative juridical legal research, which is a process of discovering legal rules, legal principles and legal doctrines in order to answer the legal issues faced. The service trade model is called the cross border mode of supply , which is a way of providing services across regional boundaries where the service provider and service recipient are in their respective countries, but the service exceeds/passes the country's territorial boundaries. Developing ICT infrastructure for e-health . Building collaboration with the private sector and profit institutions to support e-health. Develop e-health that can reach the community, especially those who are vulnerable to health problems (vulnerable) and according to their needs, Mobilize cross-sector collaboration in adopting e-health norms and standards, evaluation, cost-effectiveness principles in e-health to guarantee quality, ethics and security while still prioritizing confidentiality, privacy, equity and equality . Developing a center of excellence and e-health network , developing a public health information system model for surveillance, response and emergencies. From the formulation of the WHO resolution as mentioned above, it can be seen that the meaning of state responsibility that must be carried out by each government is very large in efforts to develop the nation's health. The government is responsible for planning, organizing, organizing, fostering and supervising the implementation of e-health services by preparing everything necessary, including health administration, legal and regulatory framework, infrastructure and resolution mechanisms. The WHO resolution requires the government to develop e-Healh to provide value. benefits for marginalized communities, especially those prone to health problems (vulnerable) and in accordance with their needs.